2011
DOI: 10.3233/jad-2011-101938
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Alterations in Amyloid-β Precursor Protein Induced by Amyloid-β Peptides

Abstract: Alzheimer's disease-associated amyloid-β (Aβ) peptide is neurotoxic as an oligomer, but not as a monomer, by an unknown mechanism. We showed previously that Aβ interacts with the amyloid-β precursor protein (AβPP), leading to caspase cleavage and cell death induction. To characterize this structure and interaction further, we purified the extracellular domain of AβPP695 (eAβPP) and its complex with Aβ oligomers (AβOs) of varying sizes, and then performed small angle X-ray scattering (SAXS). In the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 56 publications
(86 reference statements)
4
24
0
Order By: Relevance
“…This amplitude most likely varies because each pool of oligomers varies in its ability to remodel and produce eAPP-binding oligomers. Although we do not understand the remodeling process, the ratio of the amplitudes suggests that the 13-kDa Aβ1-40 can produce about 150% more oligomers that can bind eAPP, which is consistent with the conclusion of the earlier SAXS studies that demonstrated that the pools with smaller oligomers (≈20-kDa) were more efficient at binding the ectodomain than pools with larger oligomers (≈70-kDa) [18]. A value of seven for n is in surprisingly good agreement with the number of molecules bound to the eAPP fragments as estimated by SAXS.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This amplitude most likely varies because each pool of oligomers varies in its ability to remodel and produce eAPP-binding oligomers. Although we do not understand the remodeling process, the ratio of the amplitudes suggests that the 13-kDa Aβ1-40 can produce about 150% more oligomers that can bind eAPP, which is consistent with the conclusion of the earlier SAXS studies that demonstrated that the pools with smaller oligomers (≈20-kDa) were more efficient at binding the ectodomain than pools with larger oligomers (≈70-kDa) [18]. A value of seven for n is in surprisingly good agreement with the number of molecules bound to the eAPP fragments as estimated by SAXS.…”
Section: Resultssupporting
confidence: 88%
“…4D. The half-maximum point of each curve is close to the 1∶20 molar ratio which was shown to be effective at inducing conformational changes in the ectodomain of APP [18]. The similarity supports the conclusion that co-incubation of Aβ oligomers with eAPP 230–624 promotes a remodeling process that results in the preferred approximately 30-kDa size for binding to the ectodomain of APP.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The three proteins were MBP-eAPP 230-624 - a fusion protein containing maltose binding protein (MBP) and residues 230-624 of the ectodomain of APP (90-kDa) (FC4), eAPP 230-624 – a protein that contains only residues 230-624 (45-kDa)(FC2), and TRX-eAPP 575-624 – a fusion protein containing thioredoxin (TRX) and residues 575-624 of the ectodomain (20-kDa) (FC3). The proteins were produced as described in (Libeu et al, 2011). The proteins were concentrated to 2mg/ml in 20mM phosphate pH 6.5, 125mM sodium chloride, and then dissolved to a concentration of 50μg per ml in 20mM sodium acetate pH 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Thioredoxin (TRX) (FC2) and TRX-e AβPP 575–624 -a fusion protein containing thioredoxin and residues 575–624 of the ectodomain (20-kDa) (FC3)-were immobilized via amine coupling using 20 mM phosphate, 125 mM sodium chloride pH 7.4 as the running buffer. The fusion protein was produced as described in Libeu et al [42]. Thioredoxin was purchased from Sigma-Aldrich (Cat # T0910).…”
Section: Methodsmentioning
confidence: 99%